The Trades of Market Makers: An Empirical Analysis of NYSE Specialists. - Hasabrouck, Joel; Sofianos, George (Journal of Finance, 1993)
This paper presents a transaction-level empirical analysis of the trading activities of New York Stock Exchange specialists. The main findings of the analysis are the following: adjustment lags in inventories vary across stocks and are in some cases as long as one or two months; decomposition of specialist trading profits by trading horizon shows that the principal source of these profits is short term; an analysis of the dynamic relations among inventories, signed order flow, and quote changes suggests that trades in which the specialist participates have a higher immediate impact on the quotes than trades with no specialist participation.